CHD7 promotes proliferation of neural stem cells mediated by MIF. Issue 1 (December 2016) - Ohta, Shigeki; Yaguchi, Tomonori; Okuno, Hironobu; Chneiweiss, Hervé; Kawakami, Yutaka; Okano, Hideyuki
Abstract Macrophage migration inhibitory factor (MIF) plays an important role in supporting the proliferation and/or survival of murine neural stem/progenitor cells (NSPCs); however, the downstream effectors of this factor remain unknown. Here, we show that MIF increases the expression of Pax6 and Chd7 in NSPCs in vitro. During neural development, the chromatin remodeling factor Chd7 (chromatin helicase-DNA-binding protein 7) is expressed in the ventricular zone of the telencephalon of mouse brain at embryonic day 14.5, as well as in cultured NSPCs. Retroviral overexpression of Pax6 in NSPCs increased Chd7 gene expression. Lentivirally-expressed Chd7 shRNA suppressed cell proliferation and neurosphere formation, and inhibited neurogenesis in vitro, while decreasing gene expression of Hes5 and N-myc. In addition, CHD7 overexpression increased cell proliferation in human embryonic stem cell-derived NSPCs (ES-NSPCs). In Chd7 mutant fetal mouse brains, there were fewer intermediate progenitor cells (IPCs) compared to wildtype littermates, indicating that Chd7 contributes to neurogenesis in the early developmental mouse brain. Furthermore, in silico database analysis showed that, among members of the CHD family, CHD7 is highly expressed in human gliomas. Interestingly, high levels of CHD7 gene expression in human glioma initiating cells (GICs) compared to normal astrocytes were revealed and gene silencing of CHD7 decreased GIC proliferation. Collectively, our data demonstrate that CHD7 is an important factor in the proliferation and stemness maintenance of NSPCs, and CHD7 is a promising therapeutic target for the treatment of gliomas.